An economic analysis of factors affecting the adoption of napier grass in smallholder dairying in Kiambu district, Kenya. - Irungu, P. (University of Nairobi, 1998)
This study focused on the smallholder dairy farmers in Kiambu district. The aim of the study was to assess the factors that influence farmers‟ decision to adopt Napier grass and to quantitatively evaluate the impact of these factors on the adoption of planted fodder. It also aimed at recommending policy interventions that may be used to enhance the adoption of planted fodders for improved dairy production in Kenya. Data were collected in two phases through questionnaire interviews with Kiambu farmers in 1996 and 1997 and subjected to descriptive and quantitative analyses. The results of the descriptive analysis showed that the Napier grass adopters constituted 70% of the agricultural households in the sample. The adopting households had more educated heads and endowed with more farm resources (land and cattle) than the non-adopting households. The sample households sold Napier grass, maize stover, cut grass and banana stems in informal fodder markets where the type, seasonal availability and the quantity of fodder bought determined the prices. An opportunity cost analysis carried out using the 1997 data indicated that farmers in the sample would obtain more returns if they devoted their land to maize rather than to Napier production. The quantitative analysis used three econometric models to evaluate factors that influence the probability and the level of adoption of Napier grass among the smallholder farmers in Kiambu district. The results showed that the probability of adoption of Napier grass was positively influenced by the years of farming experience of the household head, belonging to the horticulture/dairy zone, off-farm employment, and belonging to a dairy co-operative/farmer organisation. Milk price negatively influenced the probability of adoption of Napier grass among the sample farmers. On the other hand, years of farming experience of the household head, belonging to the horticulture/dairy zone, land and cattle herd sizes, and extension advice on planted fodder had a positive impact on the level of adoption of Napier grass. Years of education of the household head had a negative effect on the level of adoption among the study farmers. The probability and the level of adoption of Napier grass were jointly influenced by the farming experience of the household head, land and cattle herd sizes, off-farm employment and co-operative/farmer organisation membership. In general, membership in a dairy co-operative/farmer organisation had the greatest impact on both the probability and the level of adoption of Napier, probably highlighting the importance of these organisations in the diffusion of agricultural technologies in Kiambu district. In all fitted models, the sex of the household head had no impact on either the probability or the level of adoption of Napier. (xii) Two policy recommendations were made based on the findings of this study. First, there is need to support and strengthen the existing dairy co-operative societies/farmer organisations to enable them fully participate in dairy development not only in Kiambu district but also in other dairy producing areas in Kenya. Second, the extension service should use contact farmers and encourage farmer-to-farmer exchanges to increase the adoption of planted forages in other areas of Kenya.